Teologi Lokal dalam Konteks Global - Johanes Baptista Giyana Banawiratma (GEMA TEOLOGIKA: Jurnal Teologi Kontekstual dan Filsafat Keilahian, 2016)
Abstract Today in the globalization process the poor is marginalized. This reflection is based on the Indonesian context of economic dependence and marginalization of the poor and the powerless. The analysis goes to axes of power namely state, market, and community. Market fundamentalism has penetrated into all kinds of powers in such a way that the powerless is excluded from the economic participation. The economic system is taking sides against the need of the poor people. The way of life of the early Christian gives an example how people live in common. The teaching of Jesus stresses very much on the preferential option of thepoor. The idea of the globalization from below and the multitude might be a help to move forward to face the problem of social injustice in all areas and levels. Abstrak Saat ini di dalam proses globalisasi, kaum miskin semakin terpinggirkan. Refleksi ini didasarkan pada konteks ketergantungan ekonomi dan peminggiran kaum miskin dan tak berdaya di Indonesia. Analisis ini mengarah pada poros-poros kekuasaan, yaitu: negara, pasar, dan masyarakat. Fundamentalisme pasar telah memasuki seluruh strata kekuasaan sedemikian rupa sehingga yang tak berdaya dipinggirkan dari keterlibatan ekonomi. Sistem ekonomi justru tidak berpihak terhadap kebutuhan rakyat miskin. Cara hidup orang Kristen awal memberikan contoh bagaimana komunitas hidup bersama. Ajaran Yesus menekankan untuk mendahulukan orang miskin. Gagasan tentang globalisasi dari aras bawah dan multitude mungkin menjadi pendorong untuk menghadapi masalah ketidakadilan sosial di semua bidang dan tingkatan.